Analysis of Relationship between Hard Skills & Soft Skills toward Employee Performance (The Indonesian Journal of Business Administration, 2021)
The contribution of micro, small and medium-sized enterprises (MSMEs) to the national economy cannot be under-estimated. The role of MSMEs in growing the Indonesian economy is significant. In the middle of its development, in early 2020, MSMEs in Indonesia were tested through the emergence of the COVID-19 outbreak. On the other hand, Indonesia is slowly moving into the age of modernization. To this day, the industrial revolution is once again turning into the fourth industrial revolution known as Industry 4.0. COVID-19 contributes to accelerating the Industrial Revolution. The organization needs to adapt its capacity to adapt to change and deal with new challenges. An organization would need an effective human resource strategy to deal with industry transformation challenges. Bandung Photo Studio is one example of MSME companies, established since 1982 which contributed on photography services industry which currently facing a global crisis that that threatens most MSMEs in the middle this pandemic. Diminished employee skills and leadership is becoming the most concerning issue facing Bandung Photo Studio and affecting their performance. Therefore, this research was intended to find out the relationship between Skills and Employee Performance during Covid-19. Keywords: Skills, Employee Performance, COVID-19